An impact of N-glycosylation on biochemical properties of a recombinant α-amylase from Bacillus licheniformis - Assel Kiribayeva; Dmitriy Silayev; Zhiger Akishev; Kairat Baltin; Saniya Aktayeva; Yerlan Ramankulov; Bekbolat Khassenov (Heliyon, 2024)
Amylases are enzymes that are known to hydrolyze starch. High efficiency of amylolytic enzymes allows them to compete in the industry with the technology of chemical hydrolysis of starch. A Bacillus licheniformis strain with high amylolytic activity was isolated from soil and designated as T5. The gene encoding α-amylase from B. licheniformis T5 was successfully expressed in both Escherichia coli (rAmyT5-E) and Pichia pastoris (as rAmyT5-P). According to the study, the recombinant α-amylases rAmyT5-E and rAmyT5-P exhibited the highest activity at pH 6.0 and temperatures of 70 and 80 °C, respectively. Over 80% of the rAmyT5-E enzyme activity was preserved following incubation within the pH range of 5–9; the same was true for rAmyT5-P after incubation at pH 6–9. N-glycosylation reduced the thermal and pH stability of the enzyme. The specific activity and catalytic efficiency of the recombinant AmyT5 α-amylase were also diminished by N-glycosylation.